China, India and the US Rebalance to the Asia Pacific: The Geopolitics of Rising Identities. Issue 4 (1st October 2016) - Turner, Oliver
ABSTRACT: The US rebalance to the Asia Pacific is consistently interpreted as a response to China's material rise. While not entirely incorrect, this assumption – derived from an overriding faith in the explanatory significance of relative state capabilities – fails to explain why rapidly rising others, most notably India, remain absent from regional US security discourse, and why a heavy US presence in Asia predates China's ascent of the 1970s onwards. To address these problems and offer an improved explanation of what the rebalance is, how and why it has come about, and what it is designed to achieve within the context of China's rise, this analysis draws from critical geopolitics and postcolonial theory. It argues that the rebalance is best conceived as the (re)articulation of historical discourses which construct certain foreign Others like China as challenges to the ontological American self, making the rebalance an attempt to pacify a particular rising identity as much as a rising state actor. The analysis is motivated in part by the question of how the rebalance is enabled in its current form. From here, the article addresses an increasing yet regressive tendency of International Relations theory to deny studies of the 'how possible' explanatory value, encouraging their marginalisation in favour of examinations into 'why' political decisions are made.